Pengembangan kemampuan representasi matematis siswa madrasah melalui pendekatan pembelajaran Open-Ended - Zakiya, Affifatus (Maliki Interdisciplinary Journal, 2025)
Mathematical representation is a crucial component of mathematics learning, as it enables students to transform information into symbols, diagrams, graphs, or other mathematical models. Yet, instruction in madrasah often emphasizes single, procedural answers, limiting students’ opportunities to express diverse forms of representation. This study aims to examine the effectiveness of the open-ended approach in enhancing students’ representational skills, particularly in solving linear equations with one variable. A descriptive qualitative method was employed through classroom observations, representation tasks, and interviews at an Islamic junior high school in East Java. The findings reveal that open-ended learning improves students’ mathematical representation in three major forms: visual (diagrams and graphs), symbolic (algebraic models), and verbal (process descriptions). The study contributes to the literature on tadris mathematics by highlighting the value of open-solution learning and provides practical recommendations for teachers to apply open-ended strategies in topics requiring representational creativity.